Heat transfer analysis of air-mist evaporative cooling in heat sink - Fadi Alnaimat (International Journal of Thermofluids, 2022)
This paper investigates heat transfer enhancement of evaporative air-mist cooling in heat sinks. Heat transfer in heat sink is studied through the development of theoretical equations of mass, momentum, energy, and water droplets evaporation. The flow domain consists of air and water droplets entrained in the primary air phase. An experimental testing setup is built and used to examine the validity of the numerical modeling of the air-mist cooling approach. The influence of mist droplets on heat transfer and the thermal performance of the heat sink is analyzed numerically and experimentally. Investigation is carried out for Reynolds number ranging between 100 and 1500, mist volume fraction ranging between 1 and 10%, and mist droplets diameter of 10 µm. It is found that increasing the inlet mist fraction from 1% to 6% increases the heat transfer coefficient by approximately 158%. Moreover, it is found that increasing Reynolds number from 100 to 1000 increases the heat transfer coefficient by approximately 100%. This numerical investigation illustrates the effectiveness of using two-phase air-mist flow cooling of heat sinks in comparison with a single-phase air flow. This study highlights the importance of using two-phase flow for enhanced heat transfer and it contributes to the development of advanced microelectronic cooling systems.